Habitat-dependent Culicoides species composition and abundance in blue tit (Cyanistes caeruleus) nests - Garrido-Bautista, Jorge; Martínez-de la Puente, Josué; Ros-Santaella, José Luis; Pintus, Eliana; Lopezosa, Paula; Bernardo, Nicola; Comas, Mar; Moreno-Rueda, Gregorio (Parasitology, 2022)
Wild birds are hosts of Culicoides from as early on as the nesting stage when constrained to their nests. However, the environmental factors which determine the abundance and composition of Culicoides species within each bird nest are still understudied. We sampled Culicoides from Eurasian blue tit (Cyanistes caeruleus) nests found in 2 types of forests located in southern Spain. Firstly, we monitored the abundance of Culicoides species in bird nests from a dry Pyrenean oak deciduous forest and a humid mixed forest comprising Pyrenean and Holm oaks throughout 2 consecutive years. During the 3rd year, we performed a cross-fostering experiment between synchronous nests to differentiate the role of rearing environment conditions from that of the genetically determined or maternally transmitted cues released by nestlings from each forest. We found 147 female Culicoides from 5 different species in the birds' nests. The abundance of Culicoides was higher in the dry forest than in the humid forest. Culicoides abundance, species richness and prevalence were greater when the nestlings were hatched later in the season. The same pattern was observed in the cross-fostering experiment, but we did not find evidence that nestling's features determined by the forest of origin had any effect on the Culicoides collected. These results support the notion that habitat type has a strong influence on the Culicoides affecting birds in their nests, while some life history traits of birds, such as the timing of reproduction, also influence Culicoides abundance and species composition.
Keywords: Haemoproteus; biting midges; zpěvní ptáci; Seasons; Avian malaria; host selection; rozmnožování; Animals; Ceratopogonidae; vectors; avian nests; Female; Forests; Reproduction; roční období; ženské pohlaví; Songbirds; zvířata; lesy; blood-feeding insects